Unique Eomes+ NK Cell Subsets Are Present in Uterus and Decidua During Early Pregnancy - Montaldo, Elisa; Vacca, Paola; Chiossone, Laura; Croxatto, Daniele; Loiacono, Fabrizio; Martini, Stefania; Ferrero, Simone; Walzer, Thierry; Moretta, Lorenzo; Mingari, Maria Cristina (Frontiers in Immunology, 2016)
Decidual and uterine Natural Killer (NK) cells have been shown to contribute to the successful pregnancy both in humans and mice. NK cells represent “cytotoxic” group 1 innate lymphoid cells (ILCs) and are distinct from the recently described “helper” ILC1. Here we show that both in humans and mice the majority of group 1 ILC in endometrium/uterus and decidua express Eomesodermin (Eomes), thus suggesting that they are developmentally related to conventional NK cells. However, they differed from peripheral NK cells. In humans Eomes+ decidual NK cells expressed CD49a and other markers of tissue residency including CD103, integrin β7, CD9, and CD69. The expression of CD103 allows the identification of different subsets of IFNγ-producing Eomes+ NK cells. We show that TGFβ can sustain/induce CD103 and CD9 expression in decidual NK cells and decidual CD34-derived NK cells, indicating that the decidual microenvironment can instruct the phenotype of Eomes+ NK cells. In murine decidua and uterus, Eomes+ cells included CD49a-CD49b+ conventional NK cells and CD49a+ cells. Notably, Eomes+CD49a+cells were absent in spleen and liver. Decidual and uterine Eomes+CD49a+ cells could be dissected in two peculiar cell subsets according to CD49b expression. CD49a-CD49b+ cells are enriched in mature CD11bhighCD27low cells, while CD49a+CD49b- and CD49a+CD49b+ cells contain higher percentages of immature CD11blowCD27high cells, both in uterus and decidua. Moreover, Eomes+CD49a+CD49b- cells decrease during gestation, thus suggesting that this peculiar subset may be required in early pregnancy rather than on later phases. Conversely, a minor Eomes-CD49a+ ILC1 population present in decidua and uterus increases during pregnancy. CD49b-Eomes+/- cells produce mainly TNF, while CD49a-CD49b+ conventional NK cells and CD49a+CD49b+ cells produce both IFNγ and TNF. Thus, human and murine decidua contains unique subsets of group 1 ILCs, including Eomes+ and Eomes- cells, with peculiar phenotypic and functional features. Our study contributes to re-examination of the complexity of uterine and decidual ILC subsets in humans and mice and highlights the role of the decidual microenvironment in shaping the features of these cells.